Filsafat Intuisionisme dalam Pembelajaran Matematika - Memen Permata Azmi; Azwir Salam (Journal on Education, 2023)
This article is a literature review from several written sources about the importance of intuitive thinking in learning mathematics. The flow of intuitionism emphasizes construction that depends on a belief. Currently, the development of intuitionism is still significant and plays an important role in learning mathematics related to discovery. In addition, intuition can be used as a liaison from one's vision so that it can help to connect the desired object with alternative choices of ideal answers. Intuition has a role as a trigger for a formal solution or as a first step in exploring answers. Intuition also plays a role when someone needs to choose and make critical choices, make, develop, and discover new hypotheses and theories in mathematics. The intuitive and analytical frameworks cannot be separated on the grounds that they are cognitive processes that complement one another. Analytical thinking is valuable at higher skill levels and can clarify and sharpen intuition. So the subjective (intuitive) and objective (analytical) aspects should not be seen as two conflicting choices, but two related approaches.